2014
DOI: 10.1007/s10948-014-2836-1
|View full text |Cite
|
Sign up to set email alerts
|

Description of High-Temperature Superconducting State in BSLCO Compound

Abstract: In the study, we have calculated the dependence of the average value of the energy gap amplitude (G) on the hole concentration (p) and temperature (T ) for the Bi 2 Sr 2−x La x CuO 6+δ (BSLCO) superconductor. The ratio of the zero temperature energy gap to the critical temperature (R G ≡ G (0) /k B T C ) and the ratio of the energy gap to the pseudogap temperature (R G ≡ G (0) /k B T ) have been estimated on this basis. It has been found that the value of the parameter R G changes for p ∈ 0.127, 0.198 in the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…In particular, it was shown that the model allows to calculate correctly the critical temperature and the energy gap at zero Kelvin. It should be noted that the appropriate calculations were carried out for the large number of the chemical compounds, and each time obtained results were consistent with the experimental data .…”
Section: The Eliashberg Approach the Pseudogap And The Pairing Mechsupporting
confidence: 62%
“…In particular, it was shown that the model allows to calculate correctly the critical temperature and the energy gap at zero Kelvin. It should be noted that the appropriate calculations were carried out for the large number of the chemical compounds, and each time obtained results were consistent with the experimental data .…”
Section: The Eliashberg Approach the Pseudogap And The Pairing Mechsupporting
confidence: 62%
“…For example, there are great difficulties in explaining the energy gap dependence on the temperature for the lower values of δ [39,[47][48][49][50]. The issue, which is not settled, is also the origin of the pseudogap.…”
Section: Introductionmentioning
confidence: 99%
“…24 Another important contribution was given by Szczȩśniak et al in Refs. [25][26][27][28][29]. They used the ideas used by Hirsch et al [5][6][7][8][9] in order to derive an effective one-band Hamiltonian with a four-fermion potential.…”
Section: Introductionmentioning
confidence: 99%